Costa Rica After Coffee : The Co-op Era in History and Memory - Gudmundson, Lowell (Book collections on Project MUSE., 2021)
"Costa Rica after Coffee explores the political, social, and economic place occupied by the coffee industry in contemporary Costa Rican history. In this follow-up to the 1986 classic Costa Rica before Coffee, Lowell Gudmundson delves into deeply mined archival sources, alongside the individual histories of key coffee growing families, to explore the development of the coop movement, the rise of the gourmet coffee market, and the societal transformations Costa Rica has undergone as a result of the coffee industry's presence in the country. While Costa Rican coffee farmers and coops experienced a golden age of coffee profits in the 1970s and 1980s, the emergence and expansion of a gourmet coffee market in the 1990s drastically reduced harvest volumes. Meanwhile, urbanization and improved education among the Costa Rican population threatened the continuance of family coffee farms, because of the lack of both farm land and a successor generation of farmers. The last few decades have seen a rise in other industries within the country, particularly tourism, such that agricultural exports like coffee have ceased to occupy the same crucial space in the Costa Rican economy. Gudmundson argues that the fulfilment of promises of coop-era reform had the paradoxical effect of challenging the endurance of the coffee industry"--